Analysis of Differences in Delivery Outcomes of Cesarean Section Eracs Method with Conventional Methods at Hanau Hospital - Greta Selfani Gulo; Masdalina Pane; Mido Ester J. Sitorus; Donal Nababan; Heny Syapitri (Jurnal Info Sains : Informatika dan Sains, 2023)
This study aims to analyze the difference in delivery outcomes between the Cesarean Section method with the Enhanced Recovery After Cesarean Section (ERACS) approach and the conventional method at Hanau Hospital. The ERACS method is applied to improve patient recovery after cesarean section by optimizing pain management, early mobilization, and fluid management. This study used a retrospective design on data of patients undergoing Cesarean Section at Hanau Hospital during a certain period. The data collected involved variables such as duration of hospitalization, postoperative pain level, recovery time after cesarean section, and postoperative complications. Statistical analyses, including independent t-tests and chi-square tests, were used to evaluate significant differences between ERACS and conventional method groups. The results of this study are expected to provide a better understanding of the effectiveness of the ERACS method in improving labor outcomes, especially related to recovery time, pain levels, and incidence of complications. These findings may support clinical decision-making regarding the selection of optimal cesarean section methods at Hanau Regional Hospital and may provide guidance for similar health institutions.